Predictors of outcome in refractory generalized convulsive status epilepticus - Kafle, Dilli Ram (Epilepsia Open, 2020)
OBJECTIVE: Refractory status epilepticus is a serious condition in which seizure continues despite use of two antiepileptic medications. Retrospective studies have shown that 29%‐43% of SE patients progress into RSE despite treatment. Mortality following RSE is high. We aimed to evaluate the predictors of outcome in patients with RSE at a tertiary care center. METHODS: Sixty‐eight consecutive patients with RSE who presented to our hospital between February 2018 and January 2020 were evaluated for outcome. RESULT: In our study 28(41.2%), patients who failed to respond to first‐ and second‐line antiepileptic drug responded to the third‐line antiepileptic drug thus avoiding mechanical ventilation and intravenous anesthesia. Low GCS at admission (P < .001), need for mechanical ventilation and intravenous anesthesia (P = .018), and long duration of RSE before recovery (P = .035) were strongly associated with worse outcome. Duration of RSE before starting treatment (P = .147), previous history of seizure (P = .717), and age of the patient (P = .319) did not influence the outcome. SIGNIFICANCE: In our study, we prospectively evaluated patients with RSE and followed them for one month after discharge from the hospital. Unlike some of the previous studies, we identified an interesting finding whereby a significant proportion of the patients responded to the third‐line antiepileptic drug and thus avoiding the complications related to mechanical ventilation.